Activation of the cAMP-generating system by vasoactive intestinal polypeptide (VIP) in the human laryngeal malignant cell line HEp-2. Issue 12 (December 1984) - Prost, Annie; Emami, Shahin; Rosselin, Gabriel; Gespach, Christian
Abstract : In the presence of 3-isobutyi-l-methylxanthine, VIP produced a dose-related (3 × 10 −9 − 10 −7 M) increase (g-fold) in cAMP production in isolated HEp-2 cells incubated at 15°C in KRP buffer. Among the peptides structurally related to VIP, including secretin (10 −7 M), pancreatic glucagon (10 −6 M), PHI, somatostatin-14 (10 −6 M), hpGRF (10 −8 − 4 × 10 −M ), GIP (2 × 10 −7 M), only PHI (3 × 10 −7 M and above) is able to activate the cAMP-generating system in HEp-2 cells, but at 102 times lower potency. Under the same conditions, histamine (10 −3 M) was also ineffective, while PGE 2 (10 −7 − 10 −4 M) increased (0-fold) basal cAMP levels in HEp-2 cells. The VIP effect is related to the interaction os the peptide on VIP recognition sites (12SI-VIP-binding capacity), coupled to the membrane-bound adenylate cyclase. The results indicate that the transformed laryngeal cell line HEp-2 possessesa receptor-cAMP system preferentially activated by VIP (relative potencies: VIP > PHI ≫ other peptides of the secretin family), and suggest that this neuropeptide could modulate biological functions in normal laryngeal epithelia in man.